Criminal Liability of Legal Entities Under Law Number 23/010 on the Congo Digital Code - Kanowa, Obed Kongolo (Universitas Lampung, 2023)
The criminal liability of legal persons under Congolese law is not dismissed in the ordinary way. It is organized in particular by certain legal texts such as Ordinance-Law No. 23-010 of March 13, 2023 on the Congolese digital code. Thus, this study tends to determine, within the framework of this new legal text, the moral persons likely to engage their penal responsibilities, the conditions of bringing into play of this responsibility, the offenses of which the latter can commit, and finally to discuss their repressive regime. In addition to this, as part of this study, we have taken care to make some recommendations or suggestions to the legislator in order to clarify certain obscure points that we have detected in the aforementioned legal text.